Analysis Of The Value Of Struggle In The Film ‘Mencuri Raden Saleh’ (Charles Sanders Peirce's Semiotics) - Tryan Nugraha; Fauzan Heru Syahputra (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The film Mencuri Raden Saleh (2022) by Angga Dwimas Sasongko combines action, drama, and moral messages that represent the values of struggle, such as courage, solidarity, and sacrifice, through its plot, conflict, and visual symbols. As a form of mass media, film plays a role in shaping collective consciousness; therefore, this study utilizes Charles Sanders Peirce's semiotics to analyze the use of icons, indices, and symbols in constructing a meaning of struggle that is both educational and reflective for the audience. This research employs a qualitative descriptive method with a sign analysis technique consisting of representamen, object, and interpretant. Data were collected through film observation, visual documentation. The research findings indicate that the values of struggle—such as courage, solidarity, sacrifice, determination, and perseverance—are strongly represented through visual, symbolic, and narrative elements in the film. Historical symbols, such as the painting "The Arrest of Pangeran Diponegoro," further strengthen the moral and social messages. In conclusion, this film serves as an effective medium of mass communication in conveying values of struggle that are relevant to the Indonesian socio-cultural context.